If f(x)= \frac{x^2 - 1}{x^2 + 1}, find f '(x) and f "(x).


If {eq}f(x)= \frac{x^2 - 1}{x^2 + 1} {/eq}, find f '(x) and f "(x).

Quotient Rule:

For this problem, we will be using the quotient rule twice to get the first derivative and the second derivative. It is the differentiation rule that we will be using as the indicated function is a quotient of two functions and such a form of functions is differentiated using this specific rule.

Answer and Explanation:

As mentioned, we must differentiate {eq}\displaystyle f(x)= \frac{x^2 - 1}{x^2 + 1} {/eq} via the quotient rule, whose formula is shown below:

{eq}\displaystyle \frac{\mathrm{d}}{\mathrm{d}x} \left(\frac{f(x)}{g(x)} \right) = \frac{g(x)f'(x)-f(x)g'(x)}{(g(x))^2} {/eq}

Finding the first derivative:

{eq}\begin{align*} \displaystyle f(x)&= \frac{x^2 - 1}{x^2 + 1}\\ \displaystyle f'(x)&= \frac{(x^2+1)\frac{\mathrm{d}}{\mathrm{d}x}(x^2-1) - (x^2-1)\frac{\mathrm{d}}{\mathrm{d}x}(x^2 + 1)}{(x^2 + 1)^2}\\ \displaystyle f'(x)&= \frac{(x^2+1)(2x) - (x^2-1)(2x)}{(x^2 + 1)^2}\\ \displaystyle f'(x)&= \frac{2x^3+2x-2x^3+2x}{(x^2 + 1)^2}\\ \implies \displaystyle f'(x)&= \frac{4x}{(x^2 + 1)^2}\\ \end{align*} {/eq}

As the first derivative is also a quotient of two functions, the second derivative can be attained using the same derivative rule:

{eq}\begin{align*} \displaystyle f''(x)& =\frac{\mathrm{d}}{\mathrm{d}x}\left( \frac{4x}{(x^2 + 1)^2}\right) \\ \displaystyle f''(x)& =\frac{(x^2 + 1)^2(4) - (4x) (2(x^2 + 1))(2x)}{((x^2 + 1)^2)^2}\\ \displaystyle f''(x)& =\frac{(x^2 + 1) (4x^2+4-16x^2)}{(x^2 + 1)^4}\\ \implies \displaystyle f''(x)& =\frac{ -12x^2+4 }{(x^2 + 1)^3}\\ \end{align*} {/eq}

Learn more about this topic:

Quotient Rule: Formula & Examples

from Division: Help & Review

Chapter 1 / Lesson 5

Related to this Question

Explore our homework questions and answers library